Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

The resource curse: which institutions matter? - Kolstad, Ivar; Chr. Michelsens institutt (Chr. Michelsen Institute, 2007)
Two types of models are dominant in the current resource curse literature. One type of model studies the selection of entrepreneurs into rent-seeking versus productive activities. The other type analyses the use of patronage by politicians seeking re-election. The policy implications of the two models are quite different. The first model suggests that institutions governing the private sector ought to be improved. The second model suggests that institutions governing the public sector should be emphasized. This article empirically tests the impact of the private versus public sector institutions on the resource curse, using cross-country data from Sachs and Warner (1997a) and Polity IV. The main result is that only improved private sector institutions ameliorate the resource curse.
Keywords: L - english / inglês; institutions / instituições; natural resources / recursos naturais

Investigação sobre Mulher e Género no Centro de Estudos Africanos - Casimiro, Isabel Maria; Adrare, Ximena (Estudos Moçambicanos, 2005)
Os estudos sobre as relações sociais entre homens e mulheres - das relações de Género - começaram a ganhar corpo a partir de finais da década de 60 os países de língua inglesa - onde foi onstruída a categoria de Género (Gender) - mas depressa se expandiram pelo mundo. Género como categoria análitica, foi e continua a ser o resultado duma interrogação feminista no sentido de esclarecer a subalternidade e subordinação das mulheres no mundo. Trata-se de uma procura que caminhou que continua a caminhar no sentido de interrogações. Não pretendem as suas criadoras feministas o esclarecimento contemplativo por si acerca da discriminação das mulheres. Moveu-as e move-as o desejo de alterar as relações desiguais entre mulheres e homens, no âmbito de construções identitárias que marcam a discriminação entre os seres humanos baseada num poder hierárquico característico do mundo em que vivemos, com o propósito de o transformar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; institutions / instituições; ⛔ No DOI found

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições